The influence of the physical environment, topography and time on the inshore distribution of invertebrate larvae : a multi-taxon approach - Duna, Oliver Olwethu (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Coastal hydrodynamics regulate population dynamics through the distribution and dispersal of the meroplankton of many benthic invertebrates. I examined the hydrodynamics at four different sites on the south-east coast of South Africa and coupled them with larval sampling done at high temporal and spatial resolution. Day and night sampling was done at all four sites and a continuous 24 hour study was done in one site, both forms of sampling were carried out in autumn and spring. Samples were taken at two stations, 900 metres offshore and 300 metres apart, within each site. Water properties measured were depth, temperature and current velocity and direction. Plankton samples were collected using a plankton pump at various depths, from the surface, bottom and either side of the thermocline when present. A wide range of taxa (mostly bryozoans, bivalves, barnacles and decapods) was examined. 2-way ANOVAs were used to test the effects of time and depth on each taxon. In addition, multiple regression analyses were performed on each taxon to investigate the effects of hydrodynamics on the distribution of larvae. Bryozoanlarvae proved to be positively phototactic whilst bivalve veligers, barnacle larvae and decapod zoeae performed diel vertical migration. Turbulence and temperature had an effect on the vertical distribution/migration of decapod zoeae. These results highlight the role of taxon-specific responses to flow and the potential differential effects on larval retention and ultimately connectivity of benthic populations.
Keywords: Benthic animals -- Larvae; Benthic animals -- Ecology; Plankton -- Larvae